Simulation-based training program effect on pediatric nurses’ knowledge and performance regarding heel-prick during newborn blood screening test - Abdulaziz Asiri; Abeer A. Almowafy; Shimaa M. Moursy; Hanan A. Abd-Elhay; Shimaa Abdelrahim Khalaf Ahmed; Aml S. Abdelrahem; Marim T. Abo Seif; Faransa A. Ahmed (BMC Nursing)
Abstract Background One of the best ways to impart important skills to trainees is through simulation-based training, which is more reliable than the conventional clinical examination method. It is used in pediatric nursing training to allow nurses to practice and improve their clinical and conversational skills during an actual child encounter. A heel-prick is a complex psychomotor task that requires skill and knowledge from the pediatric nurse performing the procedure while applying for the National Newborn Screening Program. Aim This study aimed to assess the impact of simulation-based training on pediatric nurses’ knowledge and performance regarding the heel-prick technique used during newborn blood screening tests in select hospitals in Saudi Arabia and Egypt. Methods This study utilized an experimental pre-test and post-test design. The G*Power Program® Version 3.1.9.4 was employed to determine the sample size to fulfil the study’s objectives. The sample consisted of 50 nurses recruited from the Maternity & Children Hospital Bisha, Al-Namas General Hospital in the Kingdom of Saudi Arabia, and Pediatric Assiut University Hospital in Egypt; they were randomly divided into two groups of 25 nurses, intervention and control. The sample size was calculated assuming α level of 0.05, a β level of 0.20, and a desired power of 80%. The study was conducted from June 1st to August 30th, 2023. Two data collection instruments were used: a structured questionnaire and an observational checklist for the heel-prick technique in newborn bloodspot screening sample collection. Before the training intervention, a pre-test assessing knowledge and performance was administered. Intervention and control groups received two hours of instruction every 5 days. The researcher utilized PowerPoint presentations, videos, and interactive learning session intervention to deliver the instructional content to increase nurses’ knowledge and also employed mannequins for a newborn blood spot test simulator to train participants on performance. A post-test 1 was administered immediately after the training sessions. Additionally, post-test 2 was conducted 20 days after the study and followed up after 40 days of intervention (post-test 3). Results The study participants ranged in age from 25 to 30 years, with the majority being female. A statistically significant difference was observed in the knowledge and performance of pediatric nurses following simulation-based training. The majority of nurses demonstrated correct responses after the simulation-based learning intervention. However, the nurses’ knowledge varied, as evidenced by the mean scores of their total knowledge regarding the heel-prick for the newborn bloodspot screening test. Immediately after the learning intervention session, the mean scores were 37.86 ± 1.28 and 34.84 ± 1.22 in the experimental and control groups, respectively. At 20 days post-training, the mean scores were 40.16 ± 1.11 and 33.55 ± 1.18 in the experimental and control groups, respectively, with a highly statistically significant difference (P-value = 0.0001). Moreover, at 40 days post-training, the mean scores were 39.54 ± 1.09 and 29.66 ± 1.32 in the experimental and control groups, respectively, and a statistically significant difference was found (P-value = 0.0001). Conversely, the level of nurses’ performance before training was below average, with 52% and 56% in the experimental and control groups, respectively. Immediately after the simulation-based learning, the majority of nurses in the experimental group demonstrated a good level of performance in post-test 1, post-test 2, and post-test 3, with a statistically significant difference compared to the nurses in the control group (P-value = 0.001). Conclusion The use of newborn blood spot test simulators is useful during simulation-based training in raising the overall level of the pediatric nurses’ knowledge and performance, especially through 1, 2, & 3 post-training tests. The findings have several practical implications, and one is that pediatric nurses’ performance and knowledge concerning newborn blood screening tests should be prioritized to guarantee patient safety and quality of care in pediatric patient scenarios. It is essential for nursing trainers to effectively train pediatric nurses’ by using simulators to improve their caring knowledge and performance in educational settings. By improving nurses’ knowledge and performance, we can reduce the dangers caused by their training on real neonates; also, it can be an attractive way to train nurses when trained by simulators and ultimately enhance the overall quality of nursing services in the hospital. Clinical trial number This study was registered by Clinical Trials.gov Identifier: (NCT06685471|| https://www.clinicaltrials.gov/ ) with the clinical Trail registry (12-11-2024).